Geological structure and industrial development of Iturup Island - A. K. Naravas; V. V. Dyakonov; N. A. Pogrebs (Известия высших учебных заведений: Геология и разведка, 2025)
Background. The history of the Archipelago of Kuril Islands and its geological structure are discussed from the perspective of the development of paleovolcanic structures. The magmaticstructure of Iturup Island is analyzed. Prospects for industrial ore mineralization and industrial development are outlined. Aim. To attract the attention of investors to the problem of developing the industrial infrastructure of Iturup Island, which occupies a favorable position in this economic area. Materials and methods. Available materials on the history of exploration, geological structure, and industrial prospects of the area under study are reviewed. Results. Stratiform deposits of lead and zinc are of the same age (Oligocene), regardless of the age of the host carbonate rocks. Conclusion. The geothermal activity of Iturup Island, widely represented in its volcanic structures, is a promising site for the development of the energy industry and extraction of mineral resources.